Estudios bibliométricos de la influencia tecnológica en el desarrollo productivo sostenible en artículos publicados en SCOPUS 2012 -2016 - Soto Hernández, Jonathan (2018)
This work was a documentary study of the identity of the technology in the sustainable productive development of the artisan guilds in the database SCOPUS, approaching from the point of view of the variables: productive development and technology as a general analysis of the studies carried out by several authors. The methodology was 2 queries related to the productive development TITLE-ABS-KEY (productive AND productive) and productive And Development And Craft And Guild And (Limit-To (Pubyear, 2016) Or Limit-To (Pubyear, 2015) Or Limit-To (Pubyear, 2014) Or Limit-To (Pubyear, 2013) Or Limit-To (Pubyear, 2012)) And (Limit-To (Doctype, "ar")) in 2 phases: 1. Get information. 2. Analyze and evaluate information validating authors, articles and sources obtained. This quantitative study allowed to conclude the association of 10 authors of the article Replacing soybean for winter peas in heavy-pig diets: Productive impact of the level of protease inhibitors in the ITEA magazineTechnical Information Economica Agraria, magazine of the quartile Q3; in the case of Brazil's Cadernos de Saude Publica, it has 35% Latin American participation, and the article Precocious albion: A new interpretation of the British Industrial Revolution published in the Annual Review of Economics of 2014 highlights the influence of productive development , the importance of human capital and the quality of work associated with the high level of nutrition, better institutions and the high level of learning.